Determinants of diabetes in Bangladesh using two approaches: An analysis of the Demographic and Health Survey 2011 - Swasey, Krystal K.; Gupta, Rajat Das; Nayeem, Jannatun; Al Kibria, Gulam Muhammed (Cambridge University Press, 2022)
This article was published in The Journal of Biosocial Science [ © Cambridge University Press 2019] and the definite version is available at: https://doi.org/10.1017/S002193201900066X. The Journal's website is at: https://www.cambridge.org/core/journals/journal-of-biosocial-science/article/determinants-of-diabetes-in-bangladesh-using-two-approaches-an-analysis-of-the-demographic-and-health-survey-2011/79E90A6DD9A7AE17C3E1E9662CEF58AD